Learning Transformation: The Impact of Problem Based Learning with Mind Mapping on Learning Outcomes in Environmental Conservation Lesson - Yusniza Yusniza; Cut Nurmaliah; Abdullah Abdullah; M. Ali Sarong; Safrida Safrida (Jurnal Penelitian Pendidikan IPA, 2023)
Schools should introduce environmental conservation and change awareness centered on local issues, encouraging students to share their insights and perspectives. For this reason, this study aims to determine the effect of applying the problem-based learning model assisted by mind mapping on student learning outcomes in environmental conservation lesson. This study used a quasi-experimental design with the Pretest-Posttest Non-Equivalent Control Group Design consisting of control and experimental classes. The research population was all class X SMA Negeri 3 Banda Aceh students. Furthermore, purposive sampling produced a sample consisting of four classes with a total of 121 students. The learning outcomes data were obtained from the test instrument using 30 multiple-choice questions. Data analysis was performed using the Mann-Whitney test with a significance level 0.05. The data analysis results show that applying the problem-based learning model assisted by mind mapping has a significant effect on learning outcomes with a significance value of p < 0.05 (0.000 < 0.05). Thus, applying the problem-based learning model assisted by mind mapping positively affects learning outcomes. The results of this study provide information that problem-based learning assisted by mind mapping can be applied to conservation-based lessons.